Identifying cancer origin using circulating tumor cells. Issue 4 (2nd April 2016) - Lu, Si-Hong; Tsai, Wen-Sy; Chang, Ying-Hsu; Chou, Teh-Ying; Pang, See-Tong; Lin, Po-Hung; Tsai, Chun-Ming; Chang, Ying-Chih
ABSTRACT: Circulating tumor cells (CTCs) have become an established clinical evaluation biomarker. CTC count provides a good correlation with the prognosis of cancer patients, but has only been used with known cancer patients, and has been unable to predict the origin of the CTCs. This study demonstrates the analysis of CTCs for the identification of their primary cancer source. Twelve mL blood samples were equally dispensed on 6 CMx chips, microfluidic chips coated with an anti-EpCAM-conjugated supported lipid bilayer, for CTC capture and isolation. Captured CTCs were eluted to an immunofluorescence (IF) staining panel consisting of 6 groups of antibodies: anti-panCK, anti-CK18, anti-CK7, anti-TTF-1, anti-CK20/anti-CDX2, and anti-PSA/anti-PSMA. Cancer cell lines of lung (H1975), colorectal (DLD-1, HCT-116), and prostate (PC3, DU145, LNCaP) were selected to establish the sensitivity and specificity for distinguishing CTCs from lung, colorectal, and prostate cancer. Spiking experiments performed in 2mL of culture medium or whole blood proved the CMx platform can enumerate cancer cells of lung, colorectal, and prostate. The IF panel was tested on blood samples from lung cancer patients (n = 3), colorectal cancer patients (n = 5), prostate cancer patients (n = 5), and healthy individuals (n = 12). Peripheral blood samples found panCK + and CK18 + CTCs in lung, colorectal, and prostate cancers. CTCs expressing CK7 + or TTF-1 +, (CK20/ CDX2) +, or (PSA/ PSMA) + corresponded to lung, colorectal, or prostate cancer, respectively. In conclusion, we have designed an immunofluorescence staining panel to identify CTCs in peripheral blood to correctly identify cancer cell origin.